La venta de suelo comunero en Lima, 1990-2022 - Calderón Cockburn, Julio; Valencia León, Ivonne; Gabriel Campos, Edwin (El Colegio de México A.C., 2023)
This article discusses the submarket of informal plots on communal land in the city of Lima. The central hypothesis is that the policy of land liberalization has stimulated a greater presence of informal markets, which translates as new forms of illegality. In the case of communal property, economic agents resort to supposedly non-commercial land transfers which, in reality, seek that sellers do not share the profits on land rent with the community as a whole. These markets are mainly political, because the authorities encourage sales under political or economic profits (corruption). The methodology is embedded in a social and economic orientation, and a qualitative method and a statistical review were used.